Use of the XFEM for the design of adhesively-bonded T-joints - Raul Campilho; Filipe Moreira (Fracture and Structural Integrity)
The use of adhesive bonds greatly increased in industrial applications, as they have multiple advantages compared to other more traditional bonding methods (fastened, welded and riveted joints). The number of approaches to predict the strength of adhesive joints has increased over the years. The eXtended Finite Element Method (XFEM) is a recent variant of the (Finite Element Method) FEM to model damage growth in structures, although it is yet seldom studied within the context of bonded joints. This work consists of an experimental and XFEM analysis of aluminium alloy T-joints, adhesively-bonded with three adhesive types. A parametric study is undertaken regarding the curved adherends’ thickness (tP2), with values between 1 and 4 mm. The adhesives Araldite® AV138 (strong but brittle), Araldite® 2015 (less strong but moderately ductile) and the Sikaforce® 7752 (with the smallest strength but highly ductile) were tested. A comparative analysis between the different joints conditions was undertaken by plotting peel (sy) and shear (txy) stresses, and analysing the damage variable. The XFEM predictive capabilities were tested with different damage initiation and propagation criteria. It was found that, provided that the modelling conditions are properly set, accurate numerical results can be found.